Nonstandard Employment in the Nordics – Toward Precarious Work? - Rasmussen, Stine; Nätti, Jouko; Larsen, Trine Pernille; Ilsøe, Anna; Garde, Anne Helene (Nordic Journal of Working Life Studies, 2019)
This article examines nonstandard employment and precariousness in four Nordic countries (Denmark, Sweden, Finland and Norway). Drawing on data from the Labour Force Survey from 1995 to 2015, the article investigates and compares recent developments of nonstandard employment in the countries and analyzes whether fixed-term contracts, temporary agency work, marginal part-time work and solo self-employment have precarious elements (measured as income or job insecurity). We conclude that nonstandard employment has remained rather stable in all four countries over time. However, although nonstandard employment seems to be largely integrated in the Nordic labor markets, it still entails precarious elements in certain countries in particular. Norway and Denmark stand out as having less insecure labor markets, while Finland and Sweden have more precariousness associated with nonstandard employment. We argue that these differences are explained by differences in the institutional contexts in the countries.